2022
DOI: 10.3389/fphar.2022.965441
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dexmedetomidine versus midazolam when combined with butorphanol for sedation and analgesia during burn dressing changes: A randomized clinical trial

Abstract: Objective: The aim of this study was to compare dexmedetomidine-butorphanol (DB) and midazolam-butorphanol (MB) combinations for sedation, and analgesia in burn patients undergoing dressing changes.Methods: A total of 56 ASA I–II burn patients were included in this single-center randomized clinical trial. The ages of these patients were between 20 and 60 years. TBSA ranged from 10% to 50%. They were randomized to group DB and group MB during dressing change. In the DB group, each patient received a bolus dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Mean ephedrine consumption in midazolam and placebo arms was also not significantly different. This result was similar to results obtained by Ding et al, 1 Ghasemloo et al 17 and Griffiths et al 2 No single antiemetic drug has the full ability to prevent N/V. Therefore, combinations of antiemetics have been used for the at-risk patient.…”
Section: Limitationssupporting
confidence: 90%
See 2 more Smart Citations
“…Mean ephedrine consumption in midazolam and placebo arms was also not significantly different. This result was similar to results obtained by Ding et al, 1 Ghasemloo et al 17 and Griffiths et al 2 No single antiemetic drug has the full ability to prevent N/V. Therefore, combinations of antiemetics have been used for the at-risk patient.…”
Section: Limitationssupporting
confidence: 90%
“…This result is similar to the study conducted by Ding et al, who mentioned that at all times, except the thirteenth minute, N/V were lower in the midazolam group and a statistical difference was seen between two categories. 1 Another recent study by Ghasemloo et al found results that were similar and concluded that a bolus dose of midazolam (2 mg) was more effective than metoclopramide (10 mg) for preventing N/V in parturient patients undergoing CS under SA. They found that the frequency of intraoperative nausea and vomiting was lower in the midazolam group compared with metoclopramide (15% vs. 52.5%).…”
Section: Limitationsmentioning
confidence: 89%
See 1 more Smart Citation
“…The most common related adverse reactions to butorphanol include nausea, vomiting, and dizziness, which are also dose-dependent ( 6 , 7 ). Butorphanol has recently been widely used in outpatient surgery due to its advantages of sedative and analgesic effects with a lower degree of respiratory depression ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%